Arthroscopic Double-Locked Stitch: A New Technique for Suturing Rotator Cuff Tears - Miyazaki, Alberto N. (Elsevier, 2014)
There are a number of reasons for failed rotator cuff tear repair. In such cases the suture-tendon interface seems to be the most vulnerable area, especially when tendon degeneration is present. We describe a new technique, the arthroscopic double-locked suture, that increases the tendon fixation and has the added benefit of being placed parallel to the blood vessels, therefore avoiding damage to the tendon vascularization. The suture may be achieved by use of knots or knotless anchors and suture passers, without the need for any additional instrumentation. The new technique is especially helpful in cases in which the tendon is retracted and degeneration is present, impeding the use of the double-row technique or its transosseous equivalents.